(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2023)
The antioxidant activity of the Curuba fruit (Passiflora Mollissima) from the municipality of Pamplona (Norte de Santander) – Colombia and the application in a food matrix was determined. The fruits were collected in the municipality of Pamplona – Norte de Santander. Antioxidant activity was determined by DPPH• and ABTS methods. The results of the antioxidant activity test showed that the pulp of Curuba, by the methods of DPPH• and ABTS.+ reached values of respectively. Therefore, the pulp of Passiflora Mollissima is considered promising for designing food products due to its high antioxidant activity.